Phytochemical analysis and evaluation of antioxidant and photoprotective activities of extracts from flowers of Bromelia laciniosa (Bromeliaceae). Issue 3 (4th May 2017) - de Oliveira-Júnior, Raimundo Gonçalves; Ferraz, Christiane Adrielly Alves; Souza, Grasielly Rocha; Guimarães, Amanda Leite; de Oliveira, Ana Paula; Lima-Saraiva, Sarah Raquel Gomes de; Rolim, Larissa Araújo; Rolim-Neto, Pedro José; da Silva Almeida, Jackson Roberto Guedes
ABSTRACT: In this study, the phytochemical profile of extracts from the flowers of Bromelia laciniosa was characterized. The total phenolic and flavonoids contents were determined and the antioxidant and photoprotective activities were evaluated using in vitro assays. Phytochemical analysis demonstrated that the extracts were found to be positive for the presence of anthracene derivatives, anthraquinones, coumarins, flavonoids and tannins, lignans, mono and diterpenes. The ethanol extract (Bl-EtOH) presented the most significant total phenolic content (53.75 ± 1.25 mg GAE/g). The dichloromethane extract (Bl-CH2 Cl2 ) showed the highest flavonoid content (46.06 ± 1.18 mg CE/g). The methanol extract (Bl-MeOH) was the most effective extract in the DPPH (2, 2-diphenyl-1-picrylhydrazil) assay (EC50 141.90 ± 3.01 μg/mL). Bl-EtOH and Bl-MeOH showed higher sun protection factor at a concentration of 100 mg/L (3.38 ± 0.04 and 3.78 ± 0.11, respectively). Therefore, the extracts proved to be interesting for the development of new studies aiming their incorporation into photoprotective cosmetic formulations.